TEENAGE CADRES ELIMINATE PULMONARY TUBERCULOSIS IN KASANG PUDAK VILLAGE, DISTRICT MUARO JAMBI - Erris, Erris; Ariyadi, Bambang; Harahap, V.A Irmayanti (Yayasan Education and Social Center, 2023)
The education and skills carried out by teenagers as elimination cadres can help prevent pulmonary Tuberculosis (TB) in the community in Kasang Pudak Village, Regency of Kumpeh Ulu, District Muaro Jambi. It is done to reduce the risk of spreading Tuberculosis, TB Drug Use, Hand Hygiene and Cough Etiquette. The patient assistance that is carried out has obstacles and challenges in the community because it is tough to be able to provide education to the community of pulmonary TB patients directly; this is because they feel embarrassed and still have the principle that if many people find out that their families are pulmonary TB sufferers, they feel alienated from the community. Other. So, the approach is to go through local health workers in the Kumpeh Ulu Health Center Work Area and make an appointment to meet directly with the officers to carry out and educate the companions. Hopefully, this community service activity can be sustainable so that people can apply it in their daily lives and reduce their health status and pulmonary TB rates